Modeling of Turbine Engine Axial-Flow Compressor and Turbine Characteristics - Orkisz, M.; Stawarz, S. (Engineering Transactions, 1997)
The paper describes the concept of modeling the turbine engine axial-flow compressor and turbine characteristics by using the function of two variables. Accuracy of the proposed concept has been verified on the example of the given compressor and turbine characteristics. Good agreement between the modeling results and experimental characteristics has been achived.